2015
DOI: 10.2169/internalmedicine.54.3931
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Touch-panel Screening Tests for Detecting Mild Cognitive Impairment and Alzheimer's Disease

Abstract: Objective The increasing population of elderly people in Japan has accelerated the demand for a simple screening test to detect cognitive and affective declines in mild cognitive impairment (MCI) and the early stage of dementia. Methods We compared the cognitive and affective functions, activities of daily living (ADLs) and the results of four computerized touch-panel screening tests in 41 MCI subjects, 124 patients with Alzheimer's disease (AD) and 75 age-and gender-matched normal controls. Results All comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…In the early 1990s, 2 articles described the incorporation of touchscreen technology into cognitive assessments: the Cambridge Neuropsychological Test Automated Battery (CANTAB) [18] and the French-language Examen Cognitif par Ordinateur (ECO) [19]. Touchscreens have continued to be used for these purposes, evidenced by more recent examples delivering tests of global cognition [20] or batteries of cognitive tests [21-23] for the detection of dementia or mild cognitive impairment (MCI).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the early 1990s, 2 articles described the incorporation of touchscreen technology into cognitive assessments: the Cambridge Neuropsychological Test Automated Battery (CANTAB) [18] and the French-language Examen Cognitif par Ordinateur (ECO) [19]. Touchscreens have continued to be used for these purposes, evidenced by more recent examples delivering tests of global cognition [20] or batteries of cognitive tests [21-23] for the detection of dementia or mild cognitive impairment (MCI).…”
Section: Resultsmentioning
confidence: 99%
“…Several of the aforementioned articles have featured games or leisure activities; however, these have been designed to assess cognition [21,26], provide cognitive stimulation [37,45], or to assist in the delivery of therapeutic interventions [40,41]. Very few studies focused on games or activities purely for entertainment or leisure purposes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the TV set is acknowledged as a device closer to senior adults and their daily activities (Sauzéon et al, 2016a; Sauzéon et al, 2016b). Other studies propose a tactile interface as the most adequate interaction mechanism for elder people (Fukui et al, 2015; Deguchi et al, 2013) due to their ease of use, which does not require fine-grained motricity, even for patients with cognitive limitations and motor dysfunction. However, in the field of ICT solutions based on games for cognitive evaluation, no published results are available at the time of writing this paper discussing the evaluation of the user experience, neither based on TAM nor in other applicable methodologies.…”
Section: Discussionmentioning
confidence: 99%
“…Articles included in this meta-analysis had to meet all of the following inclusion criteria: they described a case-control study; brain computed tomography showed a hematoma in the basal ganglia and the operation was performed under a microscope; the study contained the transsylvian approach and the transtemporal cortex approach; the effect of postoperative recovery was evaluated by the Glasgow Outcome Scale (GOS) 15 or the activities of daily living (ADL) scale; 16 and the study was a high-quality case-control study (Newcastle-Ottawa Scale [NOS] score !7 points). 17 Studies were excluded if the data for inclusion were incomplete or the study consisted of duplicate cases data, hemorrhage was caused by cerebral aneurysm, arteriovenous malformation, cerebral trauma, or stroke because of tumors, and the hematoma was outside of the basal ganglia.…”
Section: Eligibility Criteria and Excluded Studiesmentioning
confidence: 99%